Problems of translating medical text- a study based on the book - Sheliyna, S. (University of Jaffna, 2019)
Translation is the process of rendering the meaning of a text from one language into another. Translation is an important factor in spreading out the knowledge and new discoveries in the medical field. It focuses on the number of subject areas, including pharmacology, medical rescue system, surgery, obstetrics, pediatrics, psychiatry, internal medicine, oncology, cardiology and other fields of specialty. Every second there is a message/news from the medical field and that news meet the need to be shared with the entire world. Today, people in Jaffna show much interest in their health and seek alternative sources of information instead of just believing whatever said by the doctor. As a result, many medical articles and books are constantly written and many of them should be translated. In this context, Rabies treatment unit is a special medical field which occupies an important place in contemporary Jaffna. Due to the increase of animal bites notably by Dogs & Cats medical officers are need to convey the information in a communicative and reader-friendly manner to the people, but most of the rabies treatment books are in English. They need to be translated. Translating a medical text from English into Tamil seeks certain procedures, strategies and techniques. This article discusses Rabies disease, importance of medical translation, problems face by the medical translator such as Linguistic Problems, Extra Linguistic Problems, Equivalence Problem, Miscellaneous Problem- Lexicons (Dictionaries, Glossary of Medical Terminology) that are not up-to-date and the ways of overcoming.
Keywords: Medical translation; Rabies Treatment; Prophylaxis; Post-Exposure Treatment; Animal bite wound